ANALISIS STRATEGI KOMUNIKASI PEMASARAN KONTEN SECRET RECIPE MELALUI MEDIA SOSIAL TIKTOK PADA GENERASI Z - Muhammad Khoiri Ramadhan; Mellisa F. Daniel (Jurnal Riset Multidisiplin Edukasi, 2025)
This study explores the marketing communication strategy of Starbucks Indonesia through its "Secret Recipe" content on the social media platform TikTok in reaching Generation Z. Using a descriptive qualitative approach, data were collected through semi-structured interviews with one internal Starbucks representative and three TikTok users from the Gen Z demographic. The findings reveal that the “Secret Recipe” is not merely a passing trend, but part of a broader marketing strategy aimed at building product personalization and emotional connection with the audience. Starbucks utilizes various TikTok features such as hashtags, music, filters, video tutorials, and collaborations with content creators to capture attention. TikTok’s algorithm contributes to expanding content reach to users aligned with the intended market segment. The study also found active consumer engagement, where users voluntarily create and share Secret Recipe content, enhancing brand presence without direct prompting from the company. This strategy reflects how trend-based, personalized, and audience-driven approaches can boost interest in products. The study offers practical insights for developing digital communication strategies for F&B brands aiming to build closer relationships with younger audiences in the social media era.